Post-Surgical Loco Regional Recurrence Of Breast Carcinoma In Iraq - Al-saiegh, Ali M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background : From the standpoint of mortality &morbidity, cancer is by far the most important clinical problem that concerns the breast today .The age adjusted incidence of new cases has been increasing steadily with increase in the incidence among the Iraqi women during the last few years . Materials &method : A prospective study was arranged to assess the occurrence of postsurgical loco-regional recurrence of breast carcinoma in the Iraqi female patients , a total number of 91 female patients were assessed during period from Dec.2000 to Dec.2002, the median period of follow up was two years. Result : Loco-regional recurrence developed in 20 patients (22%). Chest wall and axilla were the main sites of loco-regional recurrence seen in 12 (60%) and 6 (30%) patients respectively. Significant association were found regarding the duration between first complaint and surgical management (latency period), the size of primary tumour , the number of lymph nodes involved, staging , histopathology & grading of primary tumour. While the association between the rate of loco-regional recurrence and age ,education level ,socioeconomic status ,contraception history, marital state , lactation state , family history, parity , type of adjuvant therapy, type of surgery were in-significant. Conclusion: Carcinoma of the breast affecting Iraqi females at younger ages in a high & increasing rate than other studies with a higher Loco-regional recurrence rate. Significant association were found regarding latency period, staging, histopathology & grading of primary tumour. Aims Of Study: 1. To assess the incidence of post operative loco regional recurrence of breast carcinoma in Iraqi female patients. 2. To determine the significance of certain variables that may affect the loco regional recurrence rate .